Organizing permanent markets and monitoring food supplies in the Mamluk era (648-923 AH - 1250-1517 AD) (Damascus University Journal of Historical Studies, 2025)
Markets are an important socio-economic system that directly reflects the stability of the state, the most important ethics of the merchant class in society, and their reciprocal relationship with the state on the one hand, and consumers on the other. Accordingly, this research covers aspects of daily life in the Mamluk state through a study of markets, their architectural components, the sale of food commodities, the role of the Mamluks in their oversight, and the administrative and legal measures taken against violators. The research also addresses the most important factors influencing the availability of food, such as natural disasters, and their impact on the state, particularly grains, dairy products, beverages, and sweets. This study involves appointing employees tasked with monitoring and control, known as muhtasib (inspector) and urfa' (officials).
Keywords: Mamluks; markets; oversight; goods; muhtasib